Implementasi Supervisi Akademik Dalam Merespon Kebutuhan Peserta Didik Di Sma Negeri 1 Puri Mojokerto - Muhammad Nur Hakim; Muhammad Saryulis (Academicus: Journal of Teaching and Learning, 2023)
This research was conducted at SMA Negeri 1 Puri Mojokerto, which is located on Jl. Jaya Negara no. 2 Gatul, banjaragung, kec. Puri, district. Mojokerto, Supervision is a process of mentoring educators carried out by school principals with the aim of improving the professional abilities of educators in order to improve the quality of learning and maximum student learning outcomes. This study used qualitative research methods. The resource persons in this study were the principal, vice principal, and educators. This research was conducted at SMA Negeri 1 Puri Mojokerto. The subjects in this study were principals, vice principals, and educators. researchers conducted data collection using observations, interviews, and documentation of data analysis used by data triangulation. Researchers have a goal to find out the role and strategy of the principal at SMA Negeri 1 Puri Mojoker so that it can meet the needs of students. The results of this study indicate that: 1) Academic supervision is able to respond to the needs of students through teacher professionalism which is continuously improved and evaluated based on the results of supervision carried out by the principal. 2) The results of academic supervision are followed up in four ways, namely by giving examples, discussions, and training. The evaluation aspect of teachers has also been carried out in four ways, namely preparation, implementation, learning evaluation, and follow-up plans. Specifically, the follow-up plan will be adjusted to the teacher continuous competency development program (PKB), which will also be evaluated for PKG in 2021/2022.